Targeting the pregnane X receptor using microbial metabolite mimicry. Issue 4 (10th March 2020) - Dvořák, Zdeněk; Kopp, Felix; Costello, Cait M; Kemp, Jazmin S; Li, Hao; Vrzalová, Aneta; Štěpánková, Martina; Bartoňková, Iveta; Jiskrová, Eva; Poulíková, Karolína; Vyhlídalová, Barbora; Nordstroem, Lars U; et al.
Abstract: The human PXR (pregnane X receptor), a master regulator of drug metabolism, has essential roles in intestinal homeostasis and abrogating inflammation. Existing PXR ligands have substantial off‐target toxicity. Based on prior work that established microbial (indole) metabolites as PXR ligands, we proposed microbial metabolite mimicry as a novel strategy for drug discovery that allows exploiting previously unexplored parts of chemical space. Here, we report functionalized indole derivatives as first‐in‐class non‐cytotoxic PXR agonists as a proof of concept for microbial metabolite mimicry. The lead compound, FKK6 (Felix Kopp Kortagere 6), binds directly to PXR protein in solution, induces PXR‐specific target gene expression in cells, human organoids, and mice. FKK6 significantly represses pro‐inflammatory cytokine production cells and abrogates inflammation in mice expressing the human PXR gene. The development of FKK6 demonstrates for the first time that microbial metabolite mimicry is a viable strategy for drug discovery and opens the door to underexploited regions of chemical space. Synopsis: This study demonstrates that microbial metabolite mimicry can expand the chemical space in drug discovery. Chemical mimics of microbial indoles interacting with a host nuclear receptor provides a novel and non‐toxic therapeutic approach for treating inflammatory conditions of the intestine. The hybrid structure based (HSB) method utilized the interactions of both IPA and indole in the ligand‐binding domain (LBD) of PXR. The resulting pharmacophore was screened, and ranking by individual docking score resulted in core indole structures that were simplified using intermediates of their synthetic pathway. The two identified lead molecules FKK5 and FKK6 directly bound the ligand‐binding pocket of human PXR and induced a PXR‐dependent gene expression profile in cells and tissues. Mice expressing the human PXR gene (hPXR) significantly expressed PXR target genes upon dosing with FKK6. FKK6 abrogated inflammation in a chemical model of murine colitis in a PXR‐ dependent manner. Abstract : This study demonstrates that microbial metabolite mimicry can expand the chemical space in drug discovery. Chemical mimics of microbial indoles interacting with a host nuclear receptor provides a novel and non‐toxic therapeutic approach for treating inflammatory conditions of the intestine.